Mechanical bowel obstruction due to colonic hemangioma: Report of a case - Tolga DEMİRBAŞ and Necdet GÜLER and Cemil ÇALIŞKAN and Barış GÜRCÜ and Başak DOĞANAVŞARGİL and Mustafa KORKUT (Turkish Journal of Gastroenterology, 2019)
-